Watching your pain site reduces pain intensity in chronic back pain patients. (18th August 2015) - Diers, M.; Löffler, A.; Zieglgänsberger, W.; Trojan, J.
Abstract: Background: Chronic back pain (CBP) is a frequent debilitating and often treatment‐resistant disorder. The awareness of one's own body seems to be essential in pain reduction through visual input. Visual feedback of the back reduces experimental pain perception in CBP at this site and watching the back during repeated lumbar spine movements reduces movement‐evoked pain. In this study, we tested whether visual feedback alone can reduce habitual pain in CBP. Methods: In a within‐subject design, 19 CBP patients participated in an online visual feedback condition, watching one's own back. This was compared to several control conditions, such as watching a neutral object (book), a video of another person of the same sex, a picture of the own back, and keeping one's eyes closed in randomized order on five separate days. In each experimental session, participants rated habitual pain intensity and unpleasantness before and after the experimental manipulation. Results: We present evidence that visual feedback by watching the site of chronic pain on a video screen alone is sufficient to reduce habitual chronic pain. No additional manipulation or movement was necessary. Conclusions: These results suggest that online video feedback may be helpful in alleviating chronic pain.